2008
DOI: 10.1186/1751-0759-2-18
|View full text |Cite
|
Sign up to set email alerts
|

High-utilizing Crohn's disease patients under psychosomatic therapy*

Abstract: The course of Crohn's disease is influenced by psychological as well as somatic factors; especially depression seems important here. A significant drop of health care utilization demonstrates the benefit of psychological treatment in the subgroup of high-utilizing CD patients. Further studies are needed to replicate the findings of the clinical outcome in this CD subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
2
11
0
10
Order By: Relevance
“…Of 11 longitudinal studies of the effects of stress [4][5][6][7][8][9][10][11][12][13] , life events and/or depression on the course of IBD, 8 showed that stress, adverse life events and related psychological disorders worsened IBD while 3 showed no effect of these factors on the course of IBD ( table 1 ).…”
mentioning
confidence: 99%
“…Of 11 longitudinal studies of the effects of stress [4][5][6][7][8][9][10][11][12][13] , life events and/or depression on the course of IBD, 8 showed that stress, adverse life events and related psychological disorders worsened IBD while 3 showed no effect of these factors on the course of IBD ( table 1 ).…”
mentioning
confidence: 99%
“…This factor might be a reflection of the chronic aspects of CD, as described by other authors. [6][7][8][9][20][21][22] Deter et al 26 have also demonstrated that CD course is influenced by psychotherapy; this study has observed a reduction of −38.1% in illness activity, what could be associated to improvement in general state of health and quality of life of the patients.…”
Section: Discussionmentioning
confidence: 88%
“…[10][11][12][13]24,25 However, few studies have been conducted to evaluate the results of psychotherapy in these patients. 25,26 In the present study, the patients went through TBP process, under the referential from TIA. It has been considered that the systemic and transdisciplinary approach, viewing humans as bio-psycho-socio-spiritual beings, favors the comprehension of psychosomatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Of 11 longitudinal studies of the effects of stress, life events, and/or depression on the course of IBD, [10][11][12][13][14][15][16][17][18][19][20] 8 showed that stress, adverse life events, and related psychological disorders worsened IBD, 11,[13][14][15][16][17]19,20 while 3 showed no effect of these factors on its course. 10,12,18 Furthermore, the burgeoning research topic of psychoneuroimmunology has made apparent some of the humoral and neuronal routes by which mood, acting through the hypothalamus-pituitary-adrenal axis and the autonomic and enteric nervous systems, can alter the inflammatory and immune response in the gut.…”
Section: Discussionmentioning
confidence: 99%